A fuzzy approach to e-banking website quality assessment based on an integrated AHP-ELECTRE method - Kaya, Tolga; Kahraman, Cengiz (Technological and Economic Development of Economy, 2011)
Given the lack of physical constraints of retail banking; attraction, satisfaction, and retention of customers in e-banking mostly depend on the quality of service delivered by the website. Hence, effective assessment and monitoring of website quality have become prerequisites for profitable e-banking. Determining the overall quality of a banking website is a multidimensional issue that involves evaluation of information system (IS) quality, customer services quality, and product quality. The purpose of this study is to propose an e-banking website quality assessment methodology based on an integrated fuzzy AHP-ELECTRE approach. The fuzzy set theory has been developed for dealing with the problems arising from the vagueness, ambiguity, and subjectivity of human judgment. In the proposed methodology, the weights of the criteria are generated by a fuzzy AHP analysis. Next, fuzzy ELECTRE is used to assess the quality levels of the websites. In the third step, a fuzzy dominance relation approach is used to rank the alternatives. In order to show the potentials of the proposed method, a case study in Turkish banking sector is reported together with a sensitivity analysis. Article in English. E-Bankininkystės tinklapių kokybės vertinimas paremtas integruotu neapibrežtųjų aibių AHP-ELECTRE metodu Santrauka. Mažmeninės e-bankininkystės sėkmė priklauso nuo klientų aptarnavimo kokybės tinklapyje. Taigi, tinklapio kokybės stebėjimas ir vertinimas yra svarbi sąlyga e-bankininkystės pelningumui. Tinklapio kokybės nustatymas yra daugiadimensis uždavinys, kuris apima informacinės sistemos, klientų aptarnavimo ir produktų kokybę. šio tyrimo tikslas – pasiūlyti e-bankininkystės tinklapio vertinimo metodiką, paremtą integruotu neapibrežtųjų aibių AHP-ELECTRE metodu. Neapibrežtųjų aibių teorija buvo sukurta tam, kad spręsti subjektyvaus žmogiško vertinimo problemą. Siūlomoje metodikoje rodiklių reikšāmin- gumai apskaičiuojami neapibrežtųjų aibių AHP metodu, po to ELECTRE metodu ivertinamas tinklapių kokybės lygis. Toliau, taikant neapibrežtųjų aibių dominavimo teoriją, surikiuojamos alternatyvos. Metodo tinkamumas demonstruojamas atliekant Turkijos bankininkystės sektoriaus tyrimą ir jautrumo analizę. Reikšminiai žodžiai: daugiakriterinis vertinimas, e-bankininkystė, tinklapio kokybė, AHP, ELECTRE, neapibrežtų aibių dominavimo teorija.